Changes in precipitation extremes in Southeastern Tibet, China. (4th September 2015) - Zhang, Jinshan; Shen, Xingju; Wang, Baolong
Abstract: Based on daily precipitation records at five meteorological stations during 1978–2013 periods, the spatial and temporal characteristics of twelve indices of extreme precipitation in Southeastern Tibet have been investigated. Most precipitation indices do not exhibit consistent or statistically significant trends across the region. Regionally averaged total precipitation, consecutive dry days (CDD), heavy precipitation days (R10) and simple daily intensity index (SDII) have increased, but only consecutive dry days (CDD) are statistically significant. At the same time, there has been an insignificant decrease in regionally averaged very heavy precipitation days (R20), extremely heavy precipitation days (R25), consecutive wet days (CWD), very wet days (R95p) and extremely wet days (R99p), maximum 1-day precipitation amount (Rx1day), maximum 5-days precipitation amount (Rx5days) and Wet days (NW). The distribution of positive and negative slopes in the area is extremely irregular. The spatial and temporal distributions of indices of climate extremes in monthly precipitation extremes show differences. In addition, there were significant correlations between annual total precipitation and precipitation extremes, except consecutive dry days. Change of most extreme precipitation indices is affected by the South Asia summer monsoon (SASM) evolution.